Language evolution and recursion : an empirical investigation of human hierarchical processing - Martins, Mauricio de Jesus Dias, 1983- (2014)
Tese de doutoramento, Ciências Biomédicas (Neurociências), Universidade de Lisboa, Faculdade de Medicina, 2014